2018
DOI: 10.1016/j.redox.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Yap promotes hepatocellular carcinoma metastasis and mobilization via governing cofilin/F-actin/lamellipodium axis by regulation of JNK/Bnip3/SERCA/CaMKII pathways

Abstract: Despite the increasingly important role of Hippo-Yap in hepatocellular carcinoma (HCC) development and progression, little insight is available at the time regarding the specifics interaction of Yap and cancer cells migration. Here, we identified the mechanism by which tumor-intrinsic Yap deletion resulted in HCC migratory inhibition. Yap was greatly upregulated in HCC and its expression promoted the cells migration. Functional studies found that knockdown of Yap induced JNK phosphorylation which closely bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
185
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(201 citation statements)
references
References 65 publications
15
185
1
Order By: Relevance
“…4K-L). Furthermore, we also used EM to observe the ultrastructural changes in the mitochondria associated with Yap deficiency [42]. Normal mitochondria exhibited a spindle shape (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4K-L). Furthermore, we also used EM to observe the ultrastructural changes in the mitochondria associated with Yap deficiency [42]. Normal mitochondria exhibited a spindle shape (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, through excessive fission and deficient mitophagy, Mst1 enhanced ESCs apoptosis and limited its migration. The concept that fission or mitophagy modulates cell apoptosis is supported by a plethora of studies [8,51,52]. With respect to cell migration, several researchers reasoned that fission requires F-actin to form the potential contraction point at the surface of the mitochondria, which extensively consumes F-actin stress fibers, a necessary element for cell migration [53].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…With respect to cell migration, several researchers reasoned that fission requires F-actin to form the potential contraction point at the surface of the mitochondria, which extensively consumes F-actin stress fibers, a necessary element for cell migration [53]. Moreover, oxidative stress and energy deletion, as a result of bad-structured mitophagy or fission, have the ability to induce the F-actin degradation via the regulation of cofilin, a depolymerization agent of F-actin [52]. However, in the present study, we identified that HtrA2/Omi was the pro-apoptotic signal for ESC apoptosis induced by fission.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…The functional role of mitophagy has been explored in acute cardiac I/R injury [19] and chronic liver fatty disease [20]. Increased mitophagy enhances the resistance of cardiomyocytes against reperfusion stress and retards hepatocyte stenosis and apoptosis in the setting of a high-fat diet [21-22]. However, the exact role of mitophagy in renal IR injury remains controversial.…”
Section: Introductionmentioning
confidence: 99%